Children's Parenting Patterns In Forming Akhlaqul Karimah At Sanggar Learning Sungai Mulia Selangor Malaysia - M. Imam Bukhori; Fadlillah Fadlillah (Ar-rayyan: Journal Of Islamic Education, 2024)
Parenting styles play an important role in forming akhlaqul karimah, which is the main foundation for an individual's moral and spiritual development. This research aims to identify and analyze the parenting patterns applied at Sanggar Belajar Sungai Mulia, Selangor, Malaysia, in forming morals in children. A qualitative approach was used using in-depth interviews, direct observation and documentation studies. The research results show that the parenting style applied is combinative, combining democratic, religious and local cultural approaches. Parents and educators at this learning studio set an example through daily behavior, intensive religious learning, and strengthening character values ​​such as honesty, responsibility, and empathy. Apart from that, a conducive learning environment and community support also contribute to forming children's morals. This research emphasizes the importance of synergy between families, educational institutions and society in creating a generation with noble morals.